Phylogenomic Assessment of Biodiversity Using a Reference-Based Taxonomy: An Example With Horned Lizards (Phrynosoma) - Leaché, Adam D.; Davis, Hayden R.; Singhal, Sonal; Fujita, Matthew K.; Lahti, Megan E.; Zamudio, Kelly R. (Frontiers in Ecology and Evolution, 2021)
Phylogenomic investigations of biodiversity facilitate the detection of fine-scale population genetic structure and the demographic histories of species and populations. However, determining whether or not the genetic divergence measured among populations reflects species-level differentiation remains a central challenge in species delimitation. One potential solution is to compare genetic divergence between putative new species with other closely related species, sometimes referred to as a reference-based taxonomy. To be recognized as a new species, a population should be at least as divergent as other recognized species. Here, we develop a reference-based taxonomy for Horned Lizards (Phrynosoma; 17 species) using phylogenomic data (ddRADseq data) to provide a framework for delimiting species in the Greater Short-horned Lizard species complex (P. hernandesi). Previous species delimitation studies of this species complex have produced conflicting results, with morphological data suggesting that P. hernandesi consists of five species, whereas mitochondrial DNA support anywhere from 1 to 10+ species. To help address this conflict, we first estimated a time-calibrated species tree for P. hernandesi and close relatives using SNP data. These results support the paraphyly of P. hernandesi; we recommend the recognition of two species to promote a taxonomy that is consistent with species monophyly. There is strong evidence for three populations within P. hernandesi, and demographic modeling and admixture analyses suggest that these populations are not reproductively isolated, which is consistent with previous morphological analyses that suggest hybridization could be common. Finally, we characterize the population-species boundary by quantifying levels of genetic divergence for all 18 Phrynosoma species. Genetic divergence measures for western and southern populations of P. hernandesi failed to exceed those of other Phrynosoma species, but the relatively small population size estimated for the northern population causes it to appear as a relatively divergent species. These comparisons underscore the difficulties associated with putting a reference-based approach to species delimitation into practice. Nevertheless, the reference-based approach offers a promising framework for the consistent assessment of biodiversity within clades of organisms with similar life histories and ecological traits.